SYNTHESIS OF ADAPTIVE NUMBER-PULSE FUNCTIONAL CONVERTERSWITH VARIABLE BIT DEPTH - BARAN, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents and investigates, for the first time, a method for the structural synthesis of adaptive numerical-impulse functional converters with variable bit width operating in binary code. A new algorithm for their functioning is proposed, utilizing specialized parallel structures that enable efficient parallel computation at the digit and functional block levels. This significantly enhances processing speed compared to known analogs.The developed structural synthesis method is examined using the example of a control system for autonomous vehicles.The proposed methods and tools for performing arithmetic operations and computing elementary mathematical functions can serve as fundamental computational components for various functional transformations of input signals in the form of impulse streams. Numerical-impulse codes can be received from primary measurement sensors or specialized modeling devices with frequency or numerical-impulse outputs. The popularity of this method is due to the advantages of numerical-impulse or frequency-based signal representation. Specifically, signals consisting of fixed-amplitude pulses, where information is encoded in temporal or frequency parameters, exhibit high resistance to noise, shifts, and other interferences. This significantly simplifies data processing and transformation compared to other encoding types. Additionally, the transition from frequency signals to digital formats is relatively simple, making them convenient for use in sensor interfaces and control signal generation.Importantly, the developed structure allows for easy adaptation to dynamic changes in input data, ensuring a balance between accuracy, speed, and efficiency for systems that process numerical-impulse signals in real time.Preliminary practical experiments confirm the effectiveness of the proposed synthesis method in accelerating specialized integral calculations of unit impulses in measurement converters. This opens up new possibilities for developing high-performance numerical-impulse functional converters with variable bit width.
Keywords: measuring functional converters; number-pulse codes; digital integrators; parallel computing